Castrated male goat meat products: A marketing alternative - Figueroa-González, Juan José (2024)
Nowadays it is important to give added value to adult goats. The aim of this research was, first of all, to develop new products made from meat from castrated male goats to analyze their physicochemical properties. Secondly, obtain the production costs of said products. Three products were produced: a) dehydrated meat with three sodium and phosphate treatments, b) chorizo with two preparation formulations, and c) cooked ham with three phosphate formulations. The moisture, protein, fat, ash and sodium chloride content was determined for each product. The fat content in goat meat was lower (p ≤ 0.05) than that of commercial dehydrated meat. Goat chorizos presented on average less fat (2.5%) than commercial pork chorizo (15.4%) (p ≤ 0.05). Ham cooked with goat meat had a higher protein content than commercial ham. In the preparation of products with castrated male goat meat, the sodium content was reduced, when compared to commercial beef and pork products, respectively. Meat products from castrated male goats are a profitable alternative for goat farmers.